The somerset girls ebook A novel. - Foster, Lori (2020)
"Foster convincingly brings her characters to life against the idyllic backdrop of Kentucky farmland. This down-to-earth romance will especially appeal to animal lovers."—Publishers Weekly on The Somerset Girls No one knows you quite like a sister... Summer in Sunset, Kentucky, means long, hot days—and sometimes surprising new beginnings. Through it all, the ties of sisterhood will be there, guiding Autumn and Ember to the lives, and loves, they need... When they're running the animal-rescue farm they inherited from their grandparents, Autumn and Ember Somerset are perfectly in sync. At all other times, not so much. Dependable Autumn would rather curl up with a good book than paint the town red with Ember. After the disaster that was Autumn's last relationship, it's pure self-protection. But when her high school crush comes back to town with his adorable young daughter, igniting memories best left forgotten, there's only one person Autumn can turn to... Beneath Ember's free-spirited facade is a layer of deep hurt. She'll gladly nudge Autumn toward a second chance. But risk her own heart? Not likely. The closer Autumn gets to her own happily-ever-after, the more Ember wonders what she might be missing—and if it isn't her time to be bold, too. Don't miss The Love Shack , an all-new heart-stirring romance from New York Times bestselling author Lori Foster about Berkley Carr, who, while running her animal haven, must confront her past and the undeniable chemistry she shares with her neighbor in a small town determined to play matchmaker. More charming contemporaries from Lori Foster: The Little Flower Shop The Honeymoon Cottage The Somerset Girls The Summer of No Attachments Sisters of Summer's End